Vascular complications during transcatheter aortic valve implantation: The role of the vascular surgeon. (August 2020) - Filis, Konstantinos; Galyfos, George; Sigala, Fragiska; Karantzikos, Georgios; Vavouranakis, Manolis; Toutouzas, Konstantinos; Albanopoulos, Konstantinos; Zografos, Georgios
Introduction: This study compares the incidence of vascular complications and other major outcomes between patients undergoing transcatheter aortic valve implantation, with and without a standardized preoperative vascular surgeon consultation. Methods: This retrospective study evaluated all patients scheduled for transcatheter aortic valve implantation during a five-year period at a Hellenic University Hospital. Two main periods were evaluated: Group A (early period (2014–2015), without a standardized preoperative vascular surgeon consultation) and Group B (late period (2016–2018), with a standardized preoperative vascular surgeon consultation). All vascular complications as well as other major outcomes (early death, stroke, myocardial infarction, and treatment) were recorded. Univariate and multivariate analyses were also conducted. Results: Overall, 382 transcatheter aortic valve implantation procedures were conducted (Group A: n  = 115; duration = 19 months; Group B: n  = 267; duration = 41 months). Overall, 58 vascular complications were recorded (21 patients in Group A and 37 patients in Group B (18.3% versus 13.9%; P  = 0.279)). However, vascular complications that necessitated a vascular surgeon's interference were more frequent during the first period (13% versus 4.9%; P  = 0.009). Among patients with a vascular complication, early mortality was higher during the first period (14.3% versus 0%; P  = 0.034) although stroke and myocardial infarction rates were similar. Age >80 years (OR = 1.856 [1.134–3.452]; P  = 0.03) and preoperative vascular surgeon consultation (OR = 0.345 [0.132–0.756]; P  = 0.015) were the only independent predictors for vascular complications. Conclusions: A standardized preoperative evaluation by a vascular surgeon may decrease the risk for vascular complications that necessitate a repair as well as early mortality among patients undergoing transcatheter aortic valve implantation procedures.